Media Discourse of Indonesian Presidential Debates Between Joko Widodo and Prabowo Subianto in 2019 Election (Analysis Study of Norman Fairclough's Critical Discourse in Republika) - Cedin Rosyad NURDIN; Titi WIDANINGSIH; Heri BUDIANTO (Indonesia Strategic Sustainability, 2023)
Presidential candidate Joko Widodo and Prabowo Subianto used the mass media to win the 2019 presidential and vice presidential elections. Researchers chose the news on the presidential debates in the national mass media, Republika. The researcher applies qualitative research. To analyze the news, the researcher uses Norman Fairclough's Critical Discourse Analysis method. The researcher intends to reveal how Republika newspaper produces news on presidential debates, placement of news on presidential candidates, and the motive for presenting news on presidential candidate debates.The results show that Republika newspaper presents news on presidential debates through prophetic and Al-Hujurat Al-Qur'an journalism. Republika places Joko Widodo and Prabowo Subianto as worthy of being elected and are closed to the ulama. Republikapresents the debate news to encourage people to be smart voters by choosing thecandidates because of their vision and mission, rather than their appearance. Republika ismore inclined to Joko Widodo. Recommendations from the conclusion: Republikamaintains an Islamic identity, professional, independent, with journalistic loyalty to thewider community. Republika became a reference for news on the presidential election.The closeness of the elected candidate with the ulama must be maintained, even after theelection. Ulama also have to keep guarding the president as the previous supportresponsibility